Peningkatan Kapasitas Pengelolaan Keuangan Keluarga Berbasis Digital di Tamalanrea Jaya - Syamsu Alam; Ade Ikhlas Amal Alam; Try Dharsana; Rianda Ridho Hafizh Thaha; Andi Iqra Pradipta Natsir; Sumardi Lasise; Isnawati Osman; Yusrifah Adwiah Adnan (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to improve the capacity of digital-based family financial management in Tamalanrea Jaya, Makassar. This activity is motivated by the rapid development of digital technology, which has not been optimally utilized by families in the village. Through this program, the community service team from the Faculty of Economics and Business at Hasanuddin University will provide training and assistance in digital financial management, basic financial reporting, and the use of financial applications to improve operational efficiency within families. The program's implementation methods include seminars on digital financial technology, training in the use of financial applications, and assistance with implementing digital financial systems. The program's target outcomes include improving families' understanding and skills in digital-based financial management, scientific publications in reputable national journals, online media publications, and intellectual property rights. It is hoped that this program can contribute to improving the professionalism of financial management in Tamalanrea Jaya Village, enabling it to survive and thrive in the digital era and support regional economic growth.